Potential chemopreventive activities of a polyphenol rich purified extract from olive mill wastewater on colon cancer cells. (December 2016) - Bassani, Barbara; Rossi, Teresa; De Stefano, Daniela; Pizzichini, Daniele; Corradino, Paola; Macrì, Nicoletta; Noonan, Douglas M.; Albini, Adriana; Bruno, Antonino
Highlights: Olive mill wastewater (OMWW) is a waste product of olive oil, rich in polyphenols. A009 is a water soluble polyphenol extract from OMWW. Actions of polyphenols may be beneficial in preventing colon cancer. A009 inhibits growth, migration, invasion and adhesion of colon cancer cells. A009 inhibits tumour growth in vivo with promising cancer preventive properties. Abstract: Olive oil, a major feature of the Mediterranean diet, is an abundant source of phenolic compounds. Olive oil production is associated with the generation of waste material, termed 'olive mill wastewater' (OMWW), that has been reported to be enriched in soluble polyphenols. Given the known beneficial activity of polyphenols, we investigated whether the use of purified extracts from OMWW, termed A009, rich in hydroxytyrosol, might have anticancer activities on colon cancer (CC) cell lines in vitro and in vivo and could represent a chemopreventive preparation for CC. A009 from different batches inhibited proliferation, migration, invasion, adhesion, sprouting of CC cells and release of angiogenic, pro-inflammatory cytokines (VEGF, IL-8). Our data demonstrate that a novel purified, polyphenol enriched extract, obtained from food industry waste material, with similar activity than purified hydroxytyrosol but easier to produce in large quantities and with an environment-sensitive approach, has potential cancer chemopreventive properties for colon cancer cells.